RELATIONS EFFECT ON VALUE BRIMOB-POLRES IMPLIES IMAGE SERVICE AND REGIONAL POLICE - Sembiring, Fatmaita (Dinasti International Journal of Management Science, 2020)
The low image of the local police is still relatively little known as body protectors, protective, and public servants allegedly by a given value of the regional police service are still lacking in the handling of riots and unrest as well relations police Mobile Brigade-Police in areas that are still relatively poor. The purpose of this study is to describe Relationship-Police Mobile Brigade, Value Services, Police image, and examine the influence Relations-Police Mobile Brigade against Value Services and its implications on the image of the Police Daerah. Metode survey method used is a descriptive and explanatory survey. The type of investigation in this study is causality. The analysis unit of the Police Chief in the West Java Police with a sample of 35 Chief of Police. The time horizon in this study was cross-sectional and analytical methods used and the frequency distribution of path analysis. Based on the results of research and discussion, it can be found that Relationship-Police Brimob West Java Police high reactive, the value of West Java regional police services has been relatively high, the image of the local police are already relatively high. relations-Police Mobile Brigade affects the value of the service, the police service values ??affect the image of the police, Brimob relations-Police and the value of service several simultaneously affect the image of the police.